2020
DOI: 10.1103/physrevlett.125.105502
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Damage Avalanche Shape in Quasibrittle Materials and Subavalanche (Aftershock) Clusters

Abstract: Crackling dynamics is characterized by a release of incoming energy through intermittent avalanches. The shape, i.e. the internal temporal structure of these avalanches, gives insightful information about the physical processes involved. It was experimentally shown recently that progressive damage towards compressive failure of quasi-brittle materials can be mapped onto the universality class of interface depinning when considering scaling relationships between the global characteristics of the microcracking a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 61 publications
(97 reference statements)
3
15
0
Order By: Relevance
“…These authors clearly identified the discrepancy between x = 2 and x = 3 but offered no reason. We rationalize this observation and argue that avalanche exponents are modified by details of the AE experiments 45 .…”
Section: Acoustic Emission (Ae) Measurements Of Avalanches In Differesupporting
confidence: 68%
“…These authors clearly identified the discrepancy between x = 2 and x = 3 but offered no reason. We rationalize this observation and argue that avalanche exponents are modified by details of the AE experiments 45 .…”
Section: Acoustic Emission (Ae) Measurements Of Avalanches In Differesupporting
confidence: 68%
“…Furthermore, the first parts, belonging to small values of D in Figure 7 , are out of the region where the power fitting was made. The reason of this can be twofold: (i) these small values of S and D are sensitive to the choice of the threshold; and (ii) the effect of intrinsic absorption of the AE signal [ 29 , 30 , 31 ]. Indeed, it was shown in [ 29 ] that the signal intensity (defined as I ( t ) = U 2 ( t )) is influenced by an exponential decay due to intrinsic absorption factor, exp(− t/τ a ), where τ a is the characteristic time of absorption, and it was concluded that for short events ( D < τ a ) the AE duration is meaningless in terms of source mechanism [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reason of this can be twofold: (i) these small values of S and D are sensitive to the choice of the threshold; and (ii) the effect of intrinsic absorption of the AE signal [ 29 , 30 , 31 ]. Indeed, it was shown in [ 29 ] that the signal intensity (defined as I ( t ) = U 2 ( t )) is influenced by an exponential decay due to intrinsic absorption factor, exp(− t/τ a ), where τ a is the characteristic time of absorption, and it was concluded that for short events ( D < τ a ) the AE duration is meaningless in terms of source mechanism [ 29 ]. On the other hand, it is expected that in the D >> τ a limit the above distortion effect of the transfer behavior of the system can be moderate or even negligible [ 30 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations